RhBMP-2 and concomitant rapid material degradation synergistically promote bone repair and regeneration with collagen–hydroxyapatite nanocomposites. Issue 26 (21st June 2018) - Su, Wen; Ma, Xiaomin; Sun, Zhe; Yi, Zeng; Cui, Xinxing; Chen, Guangcan; Chen, Xiangyu; Guo, Bo; Li, Xudong
Abstract : Enhanced bone repair and regeneration were achieved by rhBMP-2 and concomitant rapid material degradation of collagen–hydroxyapatite nanocomposites. Abstract : The effective treatment of bone defects is still a great challenge in clinical practice. Synthetic bone-grafting substitutes of composition and structure analogous to bone as well as incorporated with growth factors are considered to be a promising solution. In this study, a collagen–hydroxyapatite (CHA) nanocomposite scaffold was developed by collagen self-assembly with simultaneous HA synthesis. The physicochemical properties such as morphology, inorganic phase, thermal decomposition, specific surface area and pore size distribution were characterized. The osteogenicity of CHA in the absence or presence of recombinant human bone morphogenetic protein-2 (rhBMP-2) was assessed both by cell culturing and animal implantation experiments. The gene expression results showed that the osteogenic differentiation capacity of rat bone mesenchymal stem cells (rBMSCs) has been enhanced both by CHA and rhBMP-2. The efficient bone regeneration of femoral defects in rabbits was achieved with CHA and CHA pre-absorbed rhBMP-2 (CHA/B), confirmed by micro-computed tomography measurements, histological observation and immunohistochemical analyses. The CHA nanocomposite was completely degraded within 8 weeks and replaced by new bone. It was found that rhBMP-2 not only accelerated and enhanced bone formation, but also expedited the degradation of CHA. It is believed that the rhBMP-2 and concomitant rapid material degradation synergistically promote bone repair and regeneration with CHA. The biodegradation behavior of CHA in the presence of rhBMP-2 can be further investigated to gain an in-depth understanding of the complex interplays among biomaterials, growth factors and their target cells. The relevant knowledge will facilitate the search for a reasonable, safe and efficient methodology for the introduction of growth factors to biomaterials so as to achieve satisfactory tissue regeneration.